Estudo clinicopatológico de biópsias bucais em crianças e idosos: um estudo de 57 anos - Sousa, Hildecazio de Oliveira (2016)
The population growth has been observed due to a reduction in mortality and better quality of life throughout the world, with aging the most frequent consequence of this process. The falling birth rate is also another reality observed, im some countries as Brazil. Two population groups are directly related to these changes: children and elderly. These individuals presented different oral pathologies caused by various etiological factors. Although knowledge of the occurrence of the reality of these changes be important, few clinicopathological studies of the frequency of these lesions have been reported in the literature involving children and elderly. In Brazil, some studies were performed, but in small quantities. This study aimed to establish the occurrence profile of oral pathologies alterations in a population of Brazilian children and elderly, from diagnosis based on histopathological aspects of biopsies. Clinicopathological data of the lesions were retrieved and reviewed in a Brazilian population and collected information about gender, age, location and histopathological diagnoses of the lesions occurred in children (0-14 years) and elderly (≥ 60 years). Children were grouped according to the dentition, 0-5, 6-10 and 11-14 years, and the elderly were grouped 60-69, 70-79, 80-89 and ≥90 years. The lesions were categorized in non-neoplastic lesions, benign neoplasms, malignant neoplasms and potentially malignant lesions. The non-neoplastic lesions were subcategorized in: inflammatory/reactive, cysts, autoimmune conditions, bone lesions, pigmented oral lesions and others. Benign and malignant neoplasms were subcategorized according to tissue origin in: epithelial, mesenchymal, salivary gland, odontogenic tumors (benign) and other (malignant). Regarding the location, the lesions were distributed in: maxilla, mandible, buccal mucosa, lips, tongue, oral floor and not specified. A total of 10.340 biopsies were retrieved, being included in the study 8.081biopsies, 10.93% being seen in children. The female represented 54.13% of the cases (p=0.8903). Ages ranged from 0 to 14 years with an average of 9.94 years, and the group of 11-14 years, the most common (p=0.0657). Regarding location, the mandible was the most affected, with 30.02%, followed by the maxilla (25.92%) and lips (25.82%) (p=0.0133). Non-neoplastic lesions was the most common category with 80.40%, followed by benign neoplasms (18.46%) and malignant neoplasms (1.14%) (p≤0.0001). Potentially malignant lesions among children weren’t found. Among the non-neoplastic lesions, inflammatory/reactive lesions were the most common (68.61%), followed by cysts (23.52%). Among the benign neoplasms, odontogenic tumors were most common (53.37%) followed by epithelial (22.70%). Among the malingnant neoplasms were most observed mesenchymal lesions (80.00%) and salivary gland lesions (20.00%). The most common oral pathologies alterations in children were mucocele, inflammatory fibrous hyperplasia and dentigerous with 24.24%, 11.10% and 10.08%, respectively. From 8081 biopsies, 15.72% were in elderly. Female was most affected with 62.91% of the cases (p≤0.0001). The age ranged from 60 to 95 years with an average of 67.9 years, with a group of elderly with aged 60-69 the most common (p≤0.0001). Regarding the location, maxilla was the most affected, with 28.50%, followed by the mandible (24.49%) and buccal mucosa (17.64%) (p≤0.0001). Non-neoplastic lesions was the most category observed with 72.13%, followed by benign neoplasms (10.31%), malignant neoplasms (9.13%) and potentially malignant lesions (8.43%) (p≤0.0001). Among the non-neoplastic lesions, inflammatory/reactive lesions were the most common (82.86%), followed by cysts (8.30%). Among the benign neoplasms, mesenchymal tumors (38.17%) followed by epithelial tumors (32.06%) were more observed. Among the malignant tumors, epithelial lesions (88.80%) and salivary gland (6.90%) were most common. The most common oral pathologies alterations in the elderly were the inflammatory fibrous hyperplasia, oral squamous cell carcinoma, and hyperkeratosis with dysplasia with 44.17%, 6.93% and 6.77%, respectively. The study found a higher incidence of oral lesions in female children, aged 11-14 years, with non-neoplastic lesions the most common category, mainly inflammatory/reactive lesions and cysts. The most frequent lesions were mucocele, inflammatory fibrous hyperplasia and dentigerous cyst, as observed by other studies in the literature. In elderly, the study found a higher incidence of oral lesions in female, with individuals in the age group 60-69 years the most affected. Non-neoplastic lesions represented the most common category, and inflammatory/reactive the subcategory most frequent. The second subcategory most observed were malignant neoplasms of epithelial origin. The most frequent lesions were inflammatory fibrous hyperplasia, oral squamous cell carcinoma and hypekeratosis.